Enhancing Bioavailability and Stability of Curcumin Using Solid Lipid Nanoparticles (CLEN): A Covenant for Its Effectiveness - Gupta, Tanvi; Singh, Joga; Kaur, Sandeep; Sandhu, Simarjot; Singh, Gurpal; Kaur, Indu Pal (Frontiers in Bioengineering and Biotechnology, 2020)
Curcumin, very rightly referred to as “a wonder drug” is proven to be efficacious in a variety of inflammatory disorders including cancers. Antiaging, anti-inflammatory, antioxidant, antitumor, chemosensitizing, P-gp efflux inhibiting and antiproliferative activity are some of the striking features of curcumin highlighting its importance in chemotherapy. Curcumin inhibits Bcl-2, Bcl-XL, VEGF, c-Myc, ICAM-1, EGFR, STAT3 phosphorylation and cyclin D1 genes involved in the various stages of breast, prostate and gastric cancer proliferation, angiogenesis, invasion and metastasis. The full therapeutic potential of curcumin, however, remains underexplored mainly due to its poor absorption, rapid metabolism and systemic elimination all culminating in its poor bioavailability. Furthermore, curcumin is insoluble, unstable at various pH and is also prone to undergo photodegradation. Nanotechnology can help improve therapeutic potential of drug molecules with compromised biopharmaceutical profiles. Solid lipid nanoparticles are the latest offshoot of nanomedicine with proven advantages of high drug pay load, longer shelf life, biocompatibility and biodegradability, and industrial amenability of the production process. Presently, we successfully developed CLEN (Curcumin encapsulated lipidic nanoconstructs) containing 15 mg curcumin per ml of the SLN dispersion with highest (till date, to our knowledge) increase in solubility of curcumin in an aqueous system by 1.4 x 106 times as compared to its intrinsic solubility of 11 ng/ml and high drug loading (15% w/v with respect to lipid matrix). Zero-order release kinetics observed for CLEN versus first order release for free curcumin establish controlled release nature of the developed CLEN. It showed 69.78 times higher oral bioavailability with respect to free curcumin; 9.00 times higher than a bioavailable marketed formulation (Curcuwin®). The formulation showed 104, 13.3 and 10-times enhanced stability at pH 6.8, 1.2 and 7.4, respectively. All these factors can ensure elicitation of efficacy of CLEN in cancer and other inflammatory diseases.